Masyumi's "Djihad dan Qitaal" and Islamic Laws of War: Ahead of Its Time? - Muhammadin, Fajri Matahati; El-Mechwar, Fairuz (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
During the post-independence wars in Indonesia, Masyumi’s “Djihad dan Qitaal” was a book serving as a guide for the laskar (Islamic militia) in conducting jihad against those who were attempting to re-conquer Indonesia, including the Dutch and the British forces. We utilize literature research and interviews (obtaining secondary data) to examine the extent of this book’s contribution in terms of legal scholarship, particularly in the context of its historical setting (1945-1948). This research first explores the significance of “Djihad dan Qitaal” during the post-independence wars among the laskar. Second, we explore both the Islamic laws of war (fiqh al-jihad ) and the International Humanitarian Law (IHL) applicable at that time. We find that Djihad dan Qitaal” was a very important book during the war, at least in two things. First, Masyumi’s “Djihad dan Qitaal” is an important war manual used by the laskar during the post-independence wars, and it teaches Islamic laws of war as well as strengthens the spirit of jihad. Second, despite the conciseness of the book, the Islamic laws of war explained have prescribed and encouraged restraint in warfare in a way that fulfills the purpose of IHL, and is sometimes even more advanced than the IHL applicable at that time